Electrical Performance Evaluations for a Dielectric Barrier Discharge Plasma Actuator - Andrew Ragai, Henry Rigit; Lai, Koon Chun; Bong, David B L (IEEE, 2010)
Dielectric barrier discharge (DBD) plasma actuator requires an operating voltage of several kilovolts. However, during the experiment, charge accumulated on the surface of the DBD plasma actuator can reduce the electric field at the location of a microdischarge and result in current termination. This study aims to investigate the maximum voltage the actuators can withstand before the electrical breakdown happens, by varying a number of parameters include the gapping designs and dielectric thicknesses. Besides, the required threshold voltage before the microdischarges can be generated is also described in this study.